Investigations on the impact of phase change on single plume flash boiling radial expansion and drop-sizing characteristics. (5th February 2022) - Li, Xuesong; Xu, Qinglin; Qiu, Shuyi; Wang, Shangning; Hung, David; Xu, Min
Highlights: Flash boiling plume expansion is primarily caused by the expansion of the vaporized fuel. The volume fraction of the flash-boiling-vaporized fuel dominates the spray morphology. The mass fraction of the flash-boiling-vaporized fuel shows a major impact on the spray SMD. Flash boiling spray radial properties are firstly governed by near-field expansion, then far-field evaporation. The measured SMD of flash boiling spray increases with axial position due to the strong evaporation during spray penetrating. Abstract: Flash boiling atomization has been considered a promising approach to enhance spray atomization. Increasing the fuel temperature or reducing the ambient pressure can promote the phase-change of the spray, and boiling can be achieved during this process, so that spray atomization can be enhanced. However, the strong evaporative feature of flash boiling atomization induced a high vapor concentration in the plume thus changes spray characteristics. To understand the impacts of the vapor phase on spray properties in the aspects of radial expansion and drop sizing, this investigation is carried out based on a customized single-hole fuel injector with practical fuel injection settings. High-speed backlit imaging and Phase Doppler Interferometry are used to quantify the characteristics of flash boiling sprays under various boundary conditions. Macroscopic and microscopic spray morphologies were captured and it was shown that the geometry of the flash boiling spray plume was significantly impacted by the expansion of the compressed vapor phase. The evaporation of the droplets was studied by the single droplet evaporation model and the results were compared against drop sizing measurements. It was found that the evaporation and elimination of liquid droplets might affect the statistical interpretation of the drop sizing results, which is a notable feature for flash boiling sprays.